A citation network analysis of lithic microwear research. (March 2018) - Dunmore, Christopher J.; Pateman, Ben; Key, Alastair
Abstract: The introduction of lithic microwear research into the wider archaeological community by Keeley (1980) was concurrent with the development of the processual paradigm and the adoption of the scientific method. Subsequently, lithic microwear research has benefited from over 35 years of innovation, including the introduction of novel methodological and analytical procedures. The present study employs a citation network to objectively analyse the development of microwear research. Given developments in technology, as well as the institutional isolation of early microwear research, the present analysis considers the citation network that stems from Keeley's seminal 1980 volume. The 363 papers identified as having cited Keeley (1980) in the subsequent 35 years were treated as individual nodes within the citation network. Before analysis, nodes were assigned attributes, including the type of research published and whether they were supportive of three key aspects of Keeley's experimental program: the ability to determine the function of the tool and to ascertain the type of worked material from microwear, as well as the use of high-powered microscopy techniques. Emergent properties of the papers, including closeness centrality, indegree and betweenness centrality, are used to test for significant differences between paper attributes. Similarly a clustering algorithm is used to objectively define distinct clusters of important papers within the discipline. Results indicate that a small number of nodes in the network maintain statistically significant influence on the form of the citation network. These important nodes and the distinct 'schools of thought' identified are discussed in the context of Keeley's initial contribution to the sub-field. Highlights: A Citation network of lithic microwear research is objectively analysed. Centrality measures used to investigate methodological developments in the field. A minority of nodes have a significant influence on the citation network's form. Modern quantitative methodologies now form the core of the field. Calls for standardisation in the field are objectively and statistically supported.